A 1 × 48 large‐scale multi‐mode fibre optical switch. Issue 6 (7th July 2022) - Shan, Zhentian; Wan, Zhujun; Luo, Zhixiang
Abstract: A 1 × 48 large‐scale multi‐mode fibre (MMF) optical switch driven by a stepper motor is reported. The insertion loss is <1.42 dB, which can be further reduced to 1.02 dB after optimisation. With the employment of a corner cube prism in the optics, the device is characterised by good repeatability of <±0.01 dB. Meanwhile, the device has a fast response of <8 ms.